Islamic-Based Spiritual Capability as a Core Individual Competency for Enhancing Social Functioning: Theoretical Framework and Implications - Farid Ghazi Alatas (Senarai: Journal of Islamic Heritage and Civilization, 2025)
Social functioning is widely regarded as the central objective of social work practice, encompassing the ability of individuals, families, and communities to fulfill their social roles effectively within changing and complex environments. This article proposes a new theoretical construct called Islamic Spiritual Capability, which is presented as a foundational individual competency that provides an internal basis for achieving structured and sustainable social functioning. Through an integrative synthesis of Islamic behavioral theory, the concept of social functioning, and the capability approach, this study develops four dimensions of spiritual capability that can be operationalized within social work practice. These dimensions are further articulated into individual competency units that may serve as tools for assessment, professional training, and social intervention. Consequently, Islamic spiritual capability is positioned not only as an indicator of well-being but also as a learnable, measurable, and improvable core competency within a value-based and meaning-oriented framework for social development